Perbedaan Organizational Citizenship Behavior pada Karyawan yang Bekerja di Universitas Sanata Dharma Berdasarkan Status Kerja - Narthawie, Brenda; Widodo, Yohanes Heri (SOLUTION, 2024)
Organizational Citizenship Behavior is work behavior outside of an employee's obligations that is carried out voluntarily. If OCB is not implemented, there will be a decline in company growth, an unproductive work environment, and employees who are stagnant in growth. This study builds a hypothesis that permanent employees have a higher level of OCB than non-permanent employees, because permanent employees have more benefits, higher salaries, and are treated better by institutions or companies. This type of research is quantitative research that has a comparative research design. The subjects of the study were 95 Permanent Cleaning Employees and Non-Permanent Cleaning Employees of Sanata Dharma University. Consisting of 44 permanent employees and 51 non-permanent employees. The scale instrument used was a Likert scale of 55 questions with 4 alternative answers. The study was conducted via Google Form. The results of the study stated that there were differences in the OCB levels of permanent and non-permanent employees.